Regional Chemotherapy Infusion Via the Bronchial Artery in Combined Treatment of Non-Small Cell Lung Cancer - K. Sh. Gantsev; D. R. Isametov; D. T. Arybzhanov; K. E. Timin (Креативная хирургия и онкология)
Introduction. Chemotherapy in the form of endovascular infusion or its combination with radiotherapy is a method for treating non-small cell lung cancer (NSCLC), which raises heated discussions among specialists. This study is aimed at assessing the early results of combined treatment of NSCLC patients with selective chemotherapy infusion via the bronchial artery.Materials and methods. A retrospective analysis of treatment results for 24 patients with central pulmonary cancer hospitalized in the Shymkent Oncological Centre (Kazakhstan) during 2016–2019 was carried out. The average age of the patients was 46.4 ± 11.3 years. According to the histological study, 19 and 5 patients were diagnosed with squamous cell lung cancer and undifferentiated carcinoma, respectively. The patients were recognized as surgically incurable; three courses of neoadjuvant polychemotherapy via selective catheterization of the bronchial artery and regional intra-arterial administration of drugs were prescribed according to the DR scheme: Docetaxel 75 mg/m2 , Cisplatin 75 mg/m2 .Results and discussion. Upon completion of three courses of selective chemotherapy, 20 (83.3%) patients showed the possibility of surgical treatment: 15 patients underwent extended pulmonectomy, 5 patients underwent extendedcombined pulmonectomy with pericardial resection with intrapericardial, separate processing of the vessels of the lung root. After the surgical stage, all patients received radiation therapy to the mediastinal area at a single tumour dose of 2 Gy and a total radiation dose of 45–50 Gy. According to an analysis of the mortality and survival rates, 28-day mortality comprised 5% (1 patient, whose death occurred as a result of acute cardiovascular failure); one-year survival rate was 91.6%.Conclusions. Preliminary results of our study show that selective chemotherapy via the bronchial artery increases the frequency of surgical interventions and the overall survival of patients with inoperable pulmonary cancer.